Catalytic bioethanol conversion into aromatic hydrocarbons with hydrogen peroxide - V. F. Tretyakov; Thi Quỳnh Ny Tchan; R. M. Talyshinsky; A. M. Ilolov; N. A. Frantsuzova (Тонкие химические технологии)
The initiating action of hydrogen peroxide on the catalytical transformation of ethanol into aromatic hydrocarbons was studied. It was shown that the total yield of aromatic hydrocarbons increases with increasing time of contact and temperature, when rapid coking of the surface of the zeolite-containing catalyst HZSM-5 occurs in the absence of hydrogen. The modifying action of hydrogen peroxide by the catalyst surface hydroxylation and initiation of the rate-limiting step of ethylene oligomerization with the participation of peroxide radicals HO2 • was hypothesized.